Prognostic Role of the Activated p-AKT Molecule in Various Hematologic Malignancies and Solid Tumors: A Meta-Analysis - Yao, Zhen; Gao, Guangyu; Yang, Jiawen; Long, Yuming; Wang, Zhenzhen; Hu, Wentao; Liu, Yulong (Frontiers in Oncology, 2020)
Cancer is one of the main causes of human death worldwide. Recently, many studies have firmly established the causal relationship between oxidative stress and cancer initiation and progression. As a key protein in PI3K/Akt signaling pathway, p-AKT (phosphorylated Akt) participates in the process of oxidative stress and plays a prognostic role in various hematologic tumors and solid tumors. We conducted a comprehensive search of the PubMed, Embase and Cochrane libraries to identify studies published in the past decade involving cancer patients expressing p-AKT that reported overall survival (OS) during follow-up. In this study, 6,128 patients in total were evaluated from 29 enrolled articles, and we concluded that overexpression of p-AKT was closely related to worse OS in cancer patients with a hazard ratio (HR) of 2.33 (95% CI: 1.67–4.00). Furthermore, we conducted a subgroup analysis, and the results indicated that overexpression of p-AKT was associated with worse OS in hematological tumor (HR: 1.64, 95% CI: 1.41–1.92), and solid tumor (HR: 2.44, 95% CI: 1.61–5.26). High expression of p-AKT is related to poor prognosis of various hematologic tumors and solid tumors.